Humoral and cell-mediated immune response against the Mce2B (Rv0590/Mb0605) cell-wall protein of Mycobacterium bovis - Ferrara Muñiz, Ximena; Encinas, Micaela; Marques Da Silva, Wanderson; Garbaccio, Sergio Gabriel; Garro, Carlos Javier; Sammarruco, Romina Ayelén; Carignano, Hugo Adrian; Bianco, María Veronica; Cataldi, Angel Adrian; Zumarraga, Martin Jose; Eirin, Maria Emilia (Elsevier, 2025)
Bovine tuberculosis is a zoonotic disease with global distribution. Improved diagnosis is essential thus, research into new diagnostic reagents is valuable. The Mce2B recombinant protein was evaluated as an inducer of immune response The research involved naturally infected cattle with different immunological profiles. Moderate homology (≥ 40 %) between Mce2B of M. bovis and homologous proteins in non-tuberculous mycobacteria was corroborated, as well as the presence of epitopes restricted by the bovine leucocyte antigen class II. Despite this prediction, cell-mediated responses to Mce2B were undetectable in caudal fold tuberculin skin test (CF-TST) positive and non-infected animals. In CF-TST false-negative cattle, a minimal cell-mediated response was observed (5 %; IC 95 %: 0.13–24.9), lower than that elicited by PPDB (35 %; IC 95 %: 15,4–59,2) (p = 0.046) but identical to the recombinant Fusion Protein including ESAT-6, CFP-10, EspC antigens (5 %; IC 95 %: 34.9–96.8). Marginal humoral response (33.3 %; IC 95 %: 4.3–77.7) was observed in the non-infected group. These findings demonstrate that the Mce2B protein is not a suitable antigen for bovine tuberculosis diagnosis.